2008
DOI: 10.1007/s10856-008-3563-6
|View full text |Cite
|
Sign up to set email alerts
|

XPS and biocompatibility studies of titania film on anodized NiTi shape memory alloy

Abstract: A dense titania film is fabricated in situ on NiTi shape memory alloy (SMA) by anodic oxidation in a Na(2)SO(4) electrolyte. The microstructure of the titania film and its influence on the biocompatibility of NiTi SMA are investigated by scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), inductively coupled plasma mass spectrometry (ICPMS), hemolysis analysis, and platelet adhesion test. The results indicate that the titania film has a Ni-free zone near the surface and can effectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…Among these techniques, the thickening of the spontaneously formed natural oxide film on nitinol by anodic polarization in appropriate electrolyte solutions has resulted in improved corrosion resistance, one of the biocompatibility key-governing factors for nitinol implantation [10][11][12][13]. Also, the high voltage anodization was carried out in various electrolytes to produce thick porous layers [14].…”
Section: Electrochemical Impedance Spectroscopy (Eis)mentioning
confidence: 99%
See 1 more Smart Citation
“…Among these techniques, the thickening of the spontaneously formed natural oxide film on nitinol by anodic polarization in appropriate electrolyte solutions has resulted in improved corrosion resistance, one of the biocompatibility key-governing factors for nitinol implantation [10][11][12][13]. Also, the high voltage anodization was carried out in various electrolytes to produce thick porous layers [14].…”
Section: Electrochemical Impedance Spectroscopy (Eis)mentioning
confidence: 99%
“…Also, the high voltage anodization was carried out in various electrolytes to produce thick porous layers [14]. Anodic oxidation represents an effective way of modifying and controlling the properties of the metal surface [11][12][13]. It can be expected that thin anodic oxide films have potential for application in areas where the specific surface functionalization by thin films is essential for the quality of the metal implant application.…”
Section: Electrochemical Impedance Spectroscopy (Eis)mentioning
confidence: 99%
“…Their study indicates that the artificial sphincter SMA demonstrated no adverse influence on blood serum chemistry and exhibited an effective system performance. Chu et al [31] investigated the microstructure of the titanium film and its influence on the biocompatibility of NiTi SMA by scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), inductively coupled plasma mass spectrometry (ICPMS), hemolysis analysis, and platelet adhesion test. The results indicate that the titania film has a Ni-free zone near the surface and can effectively block the release of harmful Ni ions from the NiTi substrate in simulated body fluids.…”
Section: Corrosion Properties and Biocompatibility Of Niti-smamentioning
confidence: 99%
“…In the last two decades, researches concerning this kind of materials have been significantly advanced and oriented both to more basic aspects (such as the theoretical modelling and understanding of their martensitic transformation [2] and the structure and substructure formation of various alloys [3]), and to more technological aspects, such as to the discovery of new SMAs and their applications [4], and to the possible preparation procedures of these materials [5].…”
Section: Introductionmentioning
confidence: 99%
“…With the exception of the noticeable work of Biswas [31] in which single phase porous NiTi was prepared by a modified volume combustion route, most of the works concern the SHS mode. NiTi samples prepared by SHS were shown to have a porosity above 50% [6,7,13,26] with a high fraction of interconnected pores; reactants particle size, reactant mixing procedure and initial green density have been varied to obtain ideal porosity content and shape.…”
Section: Introductionmentioning
confidence: 99%